Histological observations on Montenegro's reaction in man - Wilson Mayrink; Antonio Pedro M. Schettini; Paul Williams; Pedro Raso; Paulo Araujo Magalhães; Antonio De Oliveira Lima; Maria Norma Melo; Carlos Alberto da Costa; Odair Genaro; Magno Dias; Marilene Suzan Marques Michalick (Revista do Instituto de Medicina Tropical de São Paulo, 1989)
The Montenegro skin test is widely used as a diagnostic method for American cutaneous leishmaniasis (ACL) but little is known about the histological changes that occur in the skin after administration of the antigen. This report is based on histological studies of biopsied material obtained, from inoculation sites, 48 hours after individuals had been given intradermal injections with a standardized Montenegro antigen. The material examined was obtained from four distinctly different test groups: naturally infected patients with parasitologically proved ACL and with positive Montenegro's reaction; individuals without previous history of ACL and not previously tested with Montenegro antigen; participants in anti-ACL vaccine trials who developed positive reactions to Montenegro antigen after vaccination; other participants in vaccine trials who had negative Montenegro responses after vaccination or had served as controls in the trials. The histological pictures of each group are described and discussed. Histologically, the reactions of vaccinated individuals were indistinguishable from those with naturally acquired infections.